Knowledge, attitude, and awareness on the protocols and trends in orthodontic retention among dental students - V M Nivedha; Nivethigaa Balakrishnan; Swapna Sreenivasagan (Wolters Kluwer Medknow Publications, 2022)
This survey aimed at evaluating the knowledge and awareness regarding the various retention protocols used in orthodontic practice. A survey has been conducted among the dental students by circulating 15 close-ended questions online to analyze the data collected on the protocols and trends in orthodontic retention. The male and female distribution among the study population was evaluated, and the retention protocols used were computed; statistical analysis was performed using SPSS software. Ninety-four percent accepted that Hawley retainers are predominantly used compared to fixed retainers. Eighty-seven percent agreed that they aim at a more stable dentition by the completion of orthodontic treatment. The Chi-square test on the knowledge of respondents on the permanent retention to be followed after orthodontic treatment to close generalized spacing is statistically not significant, P = 0.056. Within the considered limitations, it is clear that there is awareness among the dentists regarding the use of a retention appliance to ensure stability at the finish of orthodontic treatment. But the protocol for the same remains variable. Further studies can be performed to identify the effectiveness of each of the different retention protocols and their indications in various cases.